The Effect of different level of Pomegranate molasses on performance, egg quality trait, serological and hematological parameters in older laying hens: The Use of pomegranate molasses as growth promoter in poultry nutrition - Iqbal, Aamir; Bayram, Ismail; Gultepe , Eyup Eren; Uyarlar, Cangir; Õzçınar, Ümit; Cetingul, İbrahim Sadi (Progress in Nutrition, 2021)
The current study was planned to investigate the effects of pomegranate molasses (PM) on performance, egg quality and blood parameters in laying hens. A total of 240 Babcock white laying hens (58 weeks old) were divided into 5 groups (n=48) with 8 subgroups having 6 hens in each. Pomegranate molasses was added in the drinking water to experimental groups with 0 %, 0.1%, 0.25 %, 0.5%, and 1%, respectively during 4 weeks. Results showed that egg weight values were same in all groups exclude 1% pomegranate molasses group over control however no significant (P>0.05) result were observed on feed consumption, egg production, FCR, egg mass, egg yolk cholesterol, live body weights, and water consumption. Similarly during mid-study analyses, egg quality parameters were remained not significant (P>0.05) by the supplementation of pomegranate molasses while during final analyses, egg yolk color had positively (P<0.05) effect in 0.5% pomegranate molasses supplemented groups, however, yolk index showed positive (P<0.05) effect in 0.1% pomegranate molasses supplemented groups over control. Pomegranate molasses did not show positive effect on different serological parameters such as CHO, TP, LDL, HDL, GGT, AST, ALT and glucose level. Similarly, different blood parameters such as HCT, RBC, MCV, MCH, MCHC, PLT, RDWC, and MPV remained non-significant. Only hemoglobin level was increased in all experimental groups over control showing that pomegranate molasses can be used as an enhancer in animals with low hemoglobin level. Further detailed studies with multiple dose levels need to be investigated.